Hyaluronic acid-modified liposomes Potentiated in-vivo anti-hepatocellular carcinoma of icaritin - Sun, Xiaoduan; He, Zhenzhen; Lu, Ruilin; Liu, Zhongbing; Chiampanichayakul, Sawitree; Anuchapreeda, Songyot; Jiang, Jun; Tima, Singkome; Zhong, Zhirong (Frontiers in Pharmacology, 2024)
Icaritin (ICT), a promising anti-hepatocellular carcinoma (HCC) prenylated flavonoid, is hindered from being applied due to its low water solubility and high lipophilicity in poorly differentiated HCC which is associated with up-regulation of CD44 isoforms. Thus, hyaluronic acid (HA), a natural polysaccharide with high binding ability to CD44 receptors, was used to formulate a modified liposome as a novel targeted ICT-delivery system for HCC treatment. The ICT-Liposomes (Lip-ICT) with and without HA were prepared by a combined method of thin-film dispersion and post-insertion. The particle size, polydispersity (PDI), zeta potential, encapsulation efficacy (%EE), drug loading content (%DLC), and in vitro drug release profiles were investigated for physicochemical properties, whereas MTT assay was used to assess cytotoxic effects on HCC cells, HepG2, and Huh7 cells. Tumor bearing nude mice were used to evaluate the inhibitory effect of HA-Lip-ICT and Lip-ICT in vivo. Lip-ICT and HA-Lip-ICT had an average particle size of 171.2 ± 1.2 nm and 208.0 ± 3.2 nm, with a zeta potential of -13.9 ± 0.83 and -24.8 ± 0.36, respectively. The PDI resulted from Lip-ICT and HA-Lip-ICT was 0.28 ± 0.02 and 0.26 ± 0.02, respectively. HA-Lip-ICT demonstrated higher in vitro drug release when pH was dropped from 7.4 to 5.5, The 12-h release rate of ICT from liposomes increased from 30% at pH7.4 to more than 60% at pH5.5. HA-Lip-ICT displayed higher toxicity than Lip-ICT in both HCC cells, especially Huh7 with an IC50 of 34.15 ± 2.11 μM. The in vivo tissue distribution and anti-tumor experiments carried on tumor bearing nude mice indicated that HA-Lip-ICT exhibited higher tumor accumulation and achieved a tumor growth inhibition rate of 63.4 %. The nano-sized Lip-ICT was able to prolong the drug release time and showed long-term killing HCC cells ability. Following conjugation with HA, HA-Lip-ICT exhibited higher cytotoxicity, stronger tumor targeting, and tumor suppression abilities than Lip-ICT attributed to HA-CD44 ligand-receptor interaction, increasing the potential of ICT to treat HCC.